TINJAUAN HUKUM ISLAM TERHADAP POLA BAGI HASIL (MUDARABAH) PADA BUMP (STUDI KASUS DI PONDOK PESANTREN AL-LUQMANIYYAH UMBULHARJO YOGYAKARTA) - Putra, Yahya Hidayat (UIN Sunan Kalijaga Yogyakarta, 2017)
Al-Luqmaniyyah boarding business entity is an independent and well-systemed business applying the principle of mudarabah. In its operation, the BUMP (Pesantren owned enterprise) is domiciled as the owner of capital and santri and teacher as mudharib or capital manager. In mudarabah theory, there are harmonies and conditions that must be met. If one of the pillars and requirements is not met then the practice of mudarabah will be canceled or damaged. The mudarabah pattern in BUMP in Pondok Pesantren Al-Luqmaniyyah Yogyakarta akad mudarabahnya can be said not deviate from the teachings of Islamic religion, it is seen from the fulfillment of conditions and harmoniousness, conformity with Islamic principles on economic regulation (muamalah) and syari'ah business ethics. Mudarabah pattern practiced in BUMP Pondok Pesantren Al Luqmaniyyah consists of several business entities, but not all the same in applying the profit sharing pattern. There are several business entities in BUMP that apply revenue sharing principles such as revenue sharing system before deduction of operating expense from business, and others apply profit sharing principle, where profit sharing is calculated after deduction of operational cost from the business entityKata Kunci: mudharabah, Badan Usaha Milik Pesantren, revenue sharing, profit sharing